2015
DOI: 10.1038/nature15521
|View full text |Cite
|
Sign up to set email alerts
|

BCL11A enhancer dissection by Cas9-mediated in situ saturating mutagenesis

Abstract: Summary Enhancers, critical determinants of cellular identity, are commonly identified by correlative chromatin marks and gain-of-function potential, though only loss-of-function studies can demonstrate their requirement in the native genomic context. Previously we identified an erythroid enhancer of BCL11A, subject to common genetic variation associated with fetal hemoglobin (HbF) level, whose mouse ortholog is necessary for erythroid BCL11A expression. Here we develop pooled CRISPR-Cas9 guide RNA libraries t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
687
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 789 publications
(721 citation statements)
references
References 61 publications
6
687
0
4
Order By: Relevance
“…Fetal haemoglobin does not form long chains, so tricking cells into producing it could result in less clogging by red blood cells. A team of researchers including Feng Zhang of the Broad Institute in Cambridge, Massachusetts, recently showed that using CRISPR-Cas9 to make cuts in the genomic region that controls the expression of BCL11A increases the production of fetal haemoglobin 1 .…”
Section: Naturecommentioning
confidence: 99%
“…Fetal haemoglobin does not form long chains, so tricking cells into producing it could result in less clogging by red blood cells. A team of researchers including Feng Zhang of the Broad Institute in Cambridge, Massachusetts, recently showed that using CRISPR-Cas9 to make cuts in the genomic region that controls the expression of BCL11A increases the production of fetal haemoglobin 1 .…”
Section: Naturecommentioning
confidence: 99%
“…For hemoglobinopathies, gene editing strategizes shown to be successful include either induction of endogenous fetal hemoglobin 55,56 , modification of the causal β-globin gene mutation by targeted nucleases 57 or therapeutic transgene integration 58 , or a combined approach 59,60 . Inactivation of an erythroid specific enhancer of BCL11A by gene editing leads to suppression of BCL11A and up-regulation of γ-globin in erythroid lineage cells 61,62 . These gene editing strategizes are being performed in CD34+ stem and progenitor cells 63 or in induced pluripotent stem cells (iPSCs) capable of differentiating into any somatic cell type [64][65][66] .…”
Section: Recent Advances In Genetic Manipulation Technologymentioning
confidence: 99%
“…The group identified sgRNAs that caused complete knockout of BCL11A, with subsequent upregulation of HbF expression. 39 This important work provides a framework for therapeutic gene editing in hematopoietic stem cells to restore HbF expression and ameliorate the sickle cell phenotype. The particular enhancer targeted is specific to erythroid elements, thus preserving BCL11A expression in nonerythroid tissues and reducing side effects.…”
Section: Gene Therapy Protocols Using Genome Editing Technologiesmentioning
confidence: 99%